ESRA19-0491 Combined serratus anterior and parasternal plane blocks for post procedure analgesia in subcutaneous implantable cardioverter-defibrillator (S-ICD) implantation – a case report. (30th August 2019) - Phylactides, L; Avagliano, E; Elbatran, AI; Krol, A
Abstract : Background and aims: Insertion of the subcutaneous implantable cardioverter-defibrillator (S-ICD) is associated with considerable intra-operative and post-operative discomfort. It involves two incisions (left sternal edge and left lateral chest wall), the creation of a subcutaneous pocket for the pulse generator, tunnelling of the electrode from the medial to the lateral incisions and cephalad along the left sternal edge, induction of ventricular fibrillation (VF) and defibrillator testing. It is usually performed under general anaesthesia (GA) and often requires opioid analgesia. We present a case where GA was combined with regional anaesthesia for S-ICD implantation as a means of improving post-operative analgesia. Methods: A 45-year-old man with Brugada syndrome underwent elective implantation of S-ICD. Following induction of GA, serratus anterior plane (SAPB) and parasternal plane blocks were performed under ultrasound guidance for anterolateral chest wall and sternal edge analgesia respectively. Data collected post-operatively included regular pain assessments and analgesia requirements. Results: The patient required no additional analgesia in recovery. On the ward he remained pain free overnight and did not experience discomfort until 6am the following morning. He complained of moderate pain localised specifically to the site of the xiphoid incision. This was treated adequately with oral analgesia. Conclusions: The combination of serratus anterior and parasternal plane blocks provides adequate post-operative analgesia for the creation of the pocket and for tunnelling the electrode. Additional analgesic strategies may be needed to cover the xiphoid incision, while other considerations might include the timing of the block and techniques to prolong block duration.